Hall effect in organic layered conductors - Hasan, R.A.; Kartsovnik, M.V.; Peschansky, V.G. (Condensed Matter Physics, 2006)
The Hall effect in organic layered conductors with a multisheeted Fermi surfaces was considered. It is shown
that the experimental study of Hall effect and magnetoresistance anisotropy at different orientations of current
and a quantizing magnetic field relative to the layers makes it possible to determine the contribution of various
charge carriers groups to the conductivity, and to find out the character of Fermi surface anisotropy in the
plane of layers